DESIGN, MANUFACTURING, AND TESTING OF LOW- COST FORCE PLATFORM WITH 3-AXIS LOAD CELL - Muflihul Akbar, Muhammad
Force platform is an instrument to measure one of the essential parameters in biomechanical analysis, such as gait analysis, namely the ground reaction force. Presently there is no force platform manufacturer in Indonesia, so Indonesia must import from companies such as Kister and Bertec. However, the price of the offered force platforms is relatively high. In previous studies, a force platform with one measuring axis was manufactured, but this research used a three-axis load cell so that the force platform had better performance than the previous one. In this research, the load cell components are manufactured using a CNC machine, while other components use the manual machining process. The calibration process carried out using Tensilon RTF-1310 to provide a force with an absolute magnitude on the load cell so that the calibration matrix can be obtained. The data acquisition used is National Instrument-9237 which is specifically intended to take signals from the wheatstone bridge circuit contained in the load cell. The software used is SignalExpress, the official NI device for retrieving signals, and MATLAB for processing the signal data. Force platforms have been successfully manufactured and calibrated in order to measure the ground reaction forces of one's movement. The center of pressure and the free moment of human activity can also be obtained using this force platform. Thus, this force platform can assist in biomechanics analysis in finding the required data.